PENGARUH MODEL DISCOVERY LEARNING TERHADAP KETERAMPILAN MENULIS TEKS ARTIKEL ILMIAH POPULER SISWA FASE D KELAS VIII SMP NEGERI 18 PADANG - Zelfi Syafioda Yenti; Ricci Gemarni; Febrina Riska Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low level of students’ skills in writing popular scientific articles. The purpose of this study is to investigate the effect of using the Discovery Learning model on improving the writing skills of popular scientific articles among eleventh-grade students. The research method applied is an experimental approach with a quasi-experimental design in the form of a nonequivalent control group design. The population of the study consists of all eleventh-grade students, while the sample includes an experimental class taught using Discovery Learning and a control class taught through conventional instruction. The research instrument is a test of writing popular scientific articles that has been validated and tested for reliability. The findings reveal a significant difference in writing skills between the experimental and control groups. The implementation of Discovery Learning is proven to be more effective in enhancing students’ ability to write popular scientific articles.